THE ORIGIN OF PROVERBS AND SAYINGS (Academicia Globe: Inderscience Research, 2021)
The article is about proverbs, their origin and problems of defining proverbs and sayings. Proverbs and sayings, phraseology, neologisms, winged expressions and other means make speech more vivid, figurative, saturated and in this way stimulate communicative, cognitive and aesthetic motivation to master the language. Proverbs and proverbs are an element of folk art, which allows to concisely and figuratively express the folk wisdom, reflect the history and worldview of the people, their customs, traditions, habits and values.